Heated tobacco product use frequency, smoking quit attempts, and smoking reduction among Mexican adult smokers - Cruz-Jiménez, Lizeth; Barrientos-Gutiérrez, Inti; Vidaña-Pérez, Dèsirée; Gallegos-Carrillo, Katia; Arillo-Santillán, Edna; Rodríguez-Bolaños, Rosibel; Hardin, James W.; Kim, Minji; Thrasher, James F. (Tobacco induced diseases, 2024)
Heated tobacco products (HTPs) are promoted as less harmful than cigarettes; nonetheless, whether HTPs help smokers quit is uncertain. Data from 4067 Mexican adult smokers surveyed longitudinally every four months (November 2019-March 2021) were analyzed. Mixed-effects multinomial models regressed HTP use frequency (no use=reference; monthly; weekly; and daily use) on sociodemographics and tobacco/nicotine-related variables. Among participants who completed at least two surveys (n=2900) over four months, the duration of their longest smoking quit attempt (SQA) between surveys (SQAs: <30 days; ≥30 days; no SQA=reference) was regressed on HTP use frequency, and changes in the number of cigarettes smoked per day were regressed on HTP initiation between surveys, adjusting for covariates. Consistent predictors of all HTP use frequencies (monthly, weekly, or daily vs no use) were daily smoking >5 cigarettes (ARRR=1.69 [95% CI: 1.12-2.55], 1.88 [95% CI: 1.26-2.81] and 6.46 [95% CI: 3.33-12.52], respectively); e-cigarette use (ARRR =5.68 [95% CI: 3.38-9.53], 6.54 [95% CI: 4.06-10.55] and 2.59 [95% CI: 1.26-5.30]); lower HTP risk perceptions (ARRR=2.12 [95% CI: 1.50-30.00], 2.25 [95% CI: 1.63-3.10] and 2.00 [95% CI: 1.25-3.22]); exposure to HTP information inside (ARRR=2.13 [95% CI: 1.44-3.15], 2.13 [95% CI: 1.49-3.05] and 3.72 [95% CI: 2.28-6.09]) and outside stores (ARRR=2.36 [95% CI: 1.56-3.57], 2.32 [95% CI: 1.65-3.25] and 2.44 [95% CI: 1.41-4.24]) where tobacco is sold; having family (ARRR=2.46 [95% CI: 1.54-3.91], 2.90 [95% CI: 1.93-4.37] and 2.96 [95% CI: 1.52-5.77]) and friends (ARRR=5.78 [95% CI: 3.60-9.30], 4.98 [95% CI: 3.22-7.72] and 6.61 [95% CI: 2.91-15.01]) who use HTPs. HTP use frequency was not associated with quit attempts, except for monthly HTP use predicting SQAs lasting ≥30 days (ARRR=2.12 [95% CI: 1.17-3.85]). Initiation of HTP use was not associated with changes in smoking frequency. Limiting analysis to those who intend to quit smoking also yielded null results. Among Mexican adult smokers, frequency of HTP use was mostly not associated with either cessation behaviors or changes in cigarette consumption, suggesting that HTPs have limited to no effectiveness for smoking cessation.